1996
DOI: 10.1093/ije/25.3.568
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Primary Health Care Services on Under-Five Mortality in Rural Niger

Abstract: The findings are largely supportive of the key premise underlying selective primary health care interventions - that packages of basic services can be effectively mounted nationally in poor countries and have a significant impact over a short time period. In Niger, less than optimal implementation of VHT appears to have reduced the magnitude of the impact achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 16 publications
0
35
1
Order By: Relevance
“…One study was conducted in the Western Pacific region (Vietnam), two studies were conducted in the South East Asian region (Bangladesh and India) and the remaining 10 were conducted in the African region (Gambia, Kenya, Tanzania, Uganda, Niger, Nigeria, and DR Congo). Seven studies reported data on under-5 mortality, 22 17 20 21 23 31 32 Three studies reported more than one type of mortality outcome.…”
Section: Search Resultsmentioning
confidence: 99%
“…One study was conducted in the Western Pacific region (Vietnam), two studies were conducted in the South East Asian region (Bangladesh and India) and the remaining 10 were conducted in the African region (Gambia, Kenya, Tanzania, Uganda, Niger, Nigeria, and DR Congo). Seven studies reported data on under-5 mortality, 22 17 20 21 23 31 32 Three studies reported more than one type of mortality outcome.…”
Section: Search Resultsmentioning
confidence: 99%
“…More recently, several Latin American countries have invested heavily in primary care expansion with impressive results. Furthermore, several of the reforms in Latin America were implemented with a rigorous evaluation component, (Magnani et al, 1996) Niger X X (Pence et al, 2007) Ghana XXX (Hill et al, 2000) Gambia XX (Pannarunothai et al, 2000) Thailand X X X (Vapattanawong et al, 2007) Thailand XX (Wysocki et al, 1990) Southeast Asia X (Withanachchi et al, 2006) Sri Lanka X X (Fernando, 2000) Sri Lanka X X (Jayasinghe, 2004) Sri Lanka X X X X (Nair, 2004) Kerala, India X X X (Nag, 1988) Kerala, India X X (Varatharajan et al, 2004) Kerala, India X X (Aghajanian et al providing strong evidence of their effectiveness ( (Mullan & Frehywot, 2007). The integration of improved child health and chronic disease services as well as HIV diagnosis and treatment with primary care at the community level has been demonstrated to be successful in even the most resource-constrained countries and has resulted in improving geographic availability of life-saving services to rural populations.…”
Section: Effectiveness Access To and Coverage Of Health Servicesmentioning
confidence: 99%
“…In Afghanistan, where the government and its development partners have been contracting with NGOs to deliver a standardized package of primary care services, under-five mortality has declined from 257 in 2001 to 191 in 2006 (Ministry of Public Health of Afghanistan, 2008). Several additional countries reported positive impacts, generally on underfive mortality, from a range of primary care programs (Brockerhoff & Derose, 1996;Dugbatey, 1999;Hill, MacLeod, Joof, Gomez, & Walraven, 2000;Magnani et al, 1996;Pence, Nyarko, Phillips, & Debpuur, 2007;Perry, Shanklin, & Schroeder, 2003;Perry et al, 1998;Velema, Alihonou, Gandaho, & Hounye, 1991). While it is not possible to unequivocally attribute mortality reductions to primary care alone in these countries, as all of the initiatives involved multiple components, it is likely that the concerted effort to strengthen primary care services was a core contributor to the observed declines.…”
Section: Improved Healthmentioning
confidence: 99%
“…Evidence indicates that having up-to-date pediatric preventive care (e.g., well-child visits) was associated with reduced avoidable hospitalization among poor and near-poor children (Hakim and Bye, 2001), and that having better access to primary health care may lower children's visits to emergency department (Piehl et al, 2000). Therefore, to monitor growth/development and to provide timely treatment, pediatric preventive and primary health care visits are crucial (Magnani et al, 1996), and this is especially true for those infants in poor health and disadvantaged families. Prior studies have shed light on health care utilization in the first year of life in a variety of subpopulations, such as children of low income families and children with special needs (Dietz et al, 2012Farr et al, 2013;Holl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%